IT’S ALWAYS IN MY BAG, MY LITTLE TRUSTY USB - Wilken, Rowan Cameron; Kennedy, Jenny (AoIR Selected Papers of Internet Research, 2014)
This paper draws from a study we conducted to examine one particular form of ‘halfway media’ (Sterne 2007, p. 23): USB portable flash drives. Portable storage media are significant in that they are generally understood as personal media while their use often intersects and combines in complicated ways with institutional (tertiary study, for example) and corporate uses. And yet, despite their continued importance, very little is understood about their patterns of personal use. While there is a vast literature on mobile media and communications, and a smaller yet significant literature on portable music storage devices (Sterne 2012; Bull 2008) and other portable objects (Ito, Okabe and Anderson 2009), very little work has been done to date specifically on more general portable storage devices, such as USB portable flash drives, and associated practices of use. To recast Gitelman’s words (2008, p. 4), our interest, then, is in examining the ways that established media technologies are experienced and studied as contemporary subjects.